2019
DOI: 10.4273/ijvss.11.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Multi Response Optimization of Setting Process Variables in Face Milling of ZE41 Magnesium Alloy using Ranking Algorithms and ANOVA

Abstract: This study presents the optimization of machining parameters on ZE41 Mg alloy fabricated by gravity die casting and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). Focus on the optimization of machining parameters using the technique to get minimum surface roughness, cutting force, thermal stress, residual stress, chip thickness and maximum MRR. A number of machining experiments were conducted based on the L27 orthogonal array on computer numerical control vertical machining center. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Robots on account of its straightforwardness of activity used as a piece of the family unit, present-day and military purposes in like manner the horizons of this field are growing bit by bit [10][11][12][13][14][15][16]. The difficult thing is how to improve the current arranging framework which comprises four errands as recognizable proof, handling, choice and arranging with another picture preparing highlight [17][18][19][20][21][22][23][24][25][26]. In this new undertaking named item arranging robot utilizing picture handling, the robot is accustomed to picking the article and spot protests in required spots concerning its shading [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Robots on account of its straightforwardness of activity used as a piece of the family unit, present-day and military purposes in like manner the horizons of this field are growing bit by bit [10][11][12][13][14][15][16]. The difficult thing is how to improve the current arranging framework which comprises four errands as recognizable proof, handling, choice and arranging with another picture preparing highlight [17][18][19][20][21][22][23][24][25][26]. In this new undertaking named item arranging robot utilizing picture handling, the robot is accustomed to picking the article and spot protests in required spots concerning its shading [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The material properties and structure was most affected by reinforcement particles [9]. Alumina and graphite reinforcement particles were used in nickel metal matrix [10,11]. The frictional wear test was carried out on nickel metal matrix and it was concluded that reinforcement particles were used to reduce the friction coefficient [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the components used for the above applications were invariably machined and component like shafts were turned using conventional or CNC lathes. Hence, it becomes important to study about the cutting parameters involved in a turning operation and hence the present study was made [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%